Dari Dupa ke Doa: Makna Spritualitas Sembahyang King Hoo Ping dalam Tradisi Khonghucu di Lithang Bakti - Ariefa, Siti Nur; M. Ikhsan Tanggok (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This study examines the meaning of prayer in the King Hoo Ping prayer in Confucianism. This research is motivated by the author's interest in the process of carrying out the King Hoo Ping prayer ritual carried out by Confucians, which is known as a prayer to the spirits of ancestors and spirits that are no longer worshipped by their families, has spiritual and social values in Confucianism. This study uses a qualitative approach with field research methods and through participatory observation, the author also conducted interviews with Confucian clergy at Lithang Bakti Makin Pondok Cabe. In addition, the author also conducted a literature study to collect some data and information through literature relevant to the topic of the thesis. The approach used in this study is an anthropological approach. The results of the study show that there is a meaning to the King Hoo Ping prayer, which aims to honor ancestors and also strengthen the values of virtue such as devotion to ancestors and social concern.